2018
DOI: 10.1186/s12887-018-1023-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based play-assisted stimulation on developmental performances of children living in extreme poverty: a randomized single-blind controlled trial

Abstract: BackgroundChildren living with foster families in a resource-limited setting such as Ethiopia are at risk of developmental problems. It is not yet clear whether intensive home-based developmental stimulation assisted by play can reduce these problems. The main objective of this study was to examine the effects of play-assisted intervention integrated into basic services on the developmental performance of children living with foster families in extreme poverty.MethodsA randomized single-blind (investigator) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
3
29
0
2
Order By: Relevance
“…The actual social interaction within stimulating activities might improve children's behavior, and not so much the available props with which to play. This finding supports Worku and colleagues' work that reported moderate to large gains in social-emotional and language development from a home visit intervention that targeted mother-child play interaction (46). Finally, we found that caregivers who believed in physical punishment used more positive and also more negative discipline methods.…”
Section: Discussionsupporting
confidence: 90%
“…The actual social interaction within stimulating activities might improve children's behavior, and not so much the available props with which to play. This finding supports Worku and colleagues' work that reported moderate to large gains in social-emotional and language development from a home visit intervention that targeted mother-child play interaction (46). Finally, we found that caregivers who believed in physical punishment used more positive and also more negative discipline methods.…”
Section: Discussionsupporting
confidence: 90%
“…In addition factors such as poverty can be extrinsically bound to further psychosocial risk factors (Jensen, Berens, & Nelson, ), such as child maltreatment, domestic violence or stress (Giovanelli, Reynolds, Mondi, & Ou, ). With perhaps more widespread consequences, poverty will also require caregivers to allot an increased allocation of time to income generation and household duties and thus decreased opportunities for infant‐caregiver interactions and decreased access to family resources (Milteer, Ginsburg, Council On Communications And Media, & Committee On Psychosocial Aspects Of Child And Family Health, ; Worku et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed that poverty is associated with a mass of health problems of children, parental stress and strains in parent–child relationships [18–20]. For example, extreme poverty was strongly linked to restricted learning opportunities and inadequate stimulation at home [17]. We observed positive associations between socioeconomic classifications and availability of children’s books and playthings.…”
Section: Discussionmentioning
confidence: 55%
“…Gender, as an important demographic characteristic, may play a role in quality of care. For example, a previous study has reported family members show more preference to, give attention to, talk to and interact more with boys than girls in Ethiopia or other African countries [17]. Traditional concept of Chinese child-rearing behaviors was “son preference”, which meant caregivers tended to give boys preferential treatments than girls.…”
Section: Discussionmentioning
confidence: 99%